Effects of the Pregnant Prevention Skills Program on Health Literacy and Pregnant Prevention Behaviors among Students in the University - Jaidee, Chanintnara; Puratsakhan, Kachet (Health Science Journal of Thailand, 2024)
The objective of this quasi-experimental research was to examine the effects of pregnancy prevention skills development program towards health literacy and pregnant prevention behaviors among students of Thailand National Sports University (TNSU), Yala campus. The representative sample consisted of 60 students opted by purposive sampling. Those samples were female students who voluntarily enrolled to participate throughout the program. They were divided into groups of 30 namely experimental and control groups. The study emerged from June 12 - July 17, 2023. The instrument employed in the research was the pregnancy prevention skills development program incorporated the following activities: 1) skills development regarding the accession to prevent pregnancy, 2) the comprehension on how to prevent premature pregnancy, 3) improvement of communicative abilities, 4) health condition development of oneself, 5) media literacy advancement, and 6) how to make the right decision for the students to develop pregnancy prevention skills and health literacy. Data were analyzed using descriptive statistics and T-test. The result revealed that the pregnancy prevention skills development program in experimental group portrayed a higher level of health literacy and behavioral knowledge to prevent pregnancy compared to the controlled group with the statistically significant at 0.01.